2011
DOI: 10.1002/fuce.201100080
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Uncoated Stainless Steel as Proton Exchange Membrane Fuel Cell Bipolar Plates Material

Abstract: Thanks to their high conductivity, important gas tightness, good corrosion resistance, and low‐cost manufacturing pathways, stainless steels are considered as good candidates for proton exchange membrane fuel cell (PEMFC) bipolar plates materials. In this study, a proprietary alloy was identified as very promising: its initial electrical contact resistance (ECR) with the gas diffusion layer was low, while its corrosion resistance in simulated PEMFC environment was sufficient. Furthermore, the ECR did not incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Thus Chatenet et al reported on very good electrocatalytic OER properties of AISI 316 steel under alkaline conditions [26] . Different metals and steel types are since decades in the focus of interest for electrochemical applications [27,28,29] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus Chatenet et al reported on very good electrocatalytic OER properties of AISI 316 steel under alkaline conditions [26] . Different metals and steel types are since decades in the focus of interest for electrochemical applications [27,28,29] .…”
Section: Introductionmentioning
confidence: 99%
“…[ 26 ] Different metals and steel types are since decades in the focus of interest for electrochemical applications. [27][28][29] Chlorine oxidized AISI 304 steel (Cr-Ni stainless steel) was found to be a mediocre OER electrocatalyst requiring 500 mV overpotential to ensure 0.65 mA cm −2 current density in pH 7 corrected 0.1 M K 2 HPO 4 / KH 2 PO 4 solution. [ 23 ] Generally, the determined overpotentials for OER on recently developed materials in pH 7 media are relatively close to 500 mV at 1 mA cm −2 current density.…”
mentioning
confidence: 99%
“…Compared to the uncoated, as shown in Figure 6d, coated during the whole polarization (4 h) the current density was negative. According to these data, we can infer that the corrosion potential of 900-3 h is higher than the working potential of the anode, which makes it assume a cathodic protection state at the working potential of the anode, avoiding the generation of metal ions [5]. Specifically, the current density increased significantly before 700 s, and then slowly increased and stabilized during the remaining time.…”
Section: Potentiostatic Polarizationmentioning
confidence: 87%
“…Such irregular voltage changes, harsh environment, and long-term immersion of corrosive electrolyte cause severe corrosion of the metal bipolar plate. Meanwhile, metal BBPs lack corrosion resistance under the working environment of PEMFCs, which causes the degradation of fuel cell stack performance [4,5]. Besides, under some actual operating conditions of PEMFCs, especially at the anode, the corrosion of metal may also affect the lifetime of the MEA [22].…”
Section: Introductionmentioning
confidence: 99%
“…A solution 1 10 ±5 M H 2 SO 4 with 6 10 ±4 M F ± (NaF as the F ± source) [17±19, 61,62] was bubbled with air continuously and was kept at 70 C with the corrosion cell immersed in a tem-perature controlled water bath [63]. All these measurements were performed with a 273 A potentiostat (AMETEK).…”
Section: Electrochemical Measurementsmentioning
confidence: 99%